Comparative analysis of the arable land assessment systems and land prices of England and Hungary - Naárné Tóth, Zsuzsanna; Varga, Júlia (Studia Mundi – Economica, 2017)
The actuality of the topic is the unresolved situation of the land and the reform of the land evaluation. One part of the land evaluation is the soil value (term value) and the other is the value number expressing the economic factors. These two together express the true value of the land. There is still no uniformly applied land evaluation methodology in the European Union, methods differ according to the aims and techniques of the evaluation. Hence the determination of the economic value and the price of agricultural land is problematic. During our research, we examined the land evaluation methods used in Hungary and in England. Among others hence the determination of the economic value and the price of agricultural land is problematic. The similarity between the Hungarian and English land evaluation systems lies in the fact that both consider the effects of ecological and economic factors as well. In our opinion, some elements of the described methods of English land evaluation may be useful in the modernization of the Hungarian system of land evaluation.